2016
DOI: 10.1080/00313831.2016.1188145
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Some Young Adults not Graduate From Upper-Secondary School? On the Importance of Signals of Labour Market Failure

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…This article takes as its departure point a critical research tradition that focuses on how education systems and educational reforms impact on class relations (Apple 2004;Beach and Dovemark 2011;Bernstein 2000). Previous studies encompassing all parts of the education system from kindergarten through to higher education have shown that students' social class has a strong impact on factors ranging from teachers' expectations (Avis and Orr 2016) and assessment (Marcenaro-Gutierrez and Vignoles 2015) to students' educational choices (Alexiadou et al 2016) and results (Gustafsson, Katz and Österberg 2016). In this critical tradition such class inequalities are understood primarily as expressions of power and control rather than as natural differences arising from for example genetic predisposition or innate talent.…”
Section: Introductionmentioning
confidence: 99%
“…This article takes as its departure point a critical research tradition that focuses on how education systems and educational reforms impact on class relations (Apple 2004;Beach and Dovemark 2011;Bernstein 2000). Previous studies encompassing all parts of the education system from kindergarten through to higher education have shown that students' social class has a strong impact on factors ranging from teachers' expectations (Avis and Orr 2016) and assessment (Marcenaro-Gutierrez and Vignoles 2015) to students' educational choices (Alexiadou et al 2016) and results (Gustafsson, Katz and Österberg 2016). In this critical tradition such class inequalities are understood primarily as expressions of power and control rather than as natural differences arising from for example genetic predisposition or innate talent.…”
Section: Introductionmentioning
confidence: 99%
“…Detta är central faktor bakom skolans bristande likvärdighet. Kommunala förortsskolor förmår inte uppväga den allt påtagligare sociala skiktningen, utan betydelsen av elevernas familjebakgrund tenderar snarare att öka (Skolverket 2012;Gustavsson, Katz & Österberg 2017;Gustafsson & Yang Hansen 2018;Lindbäck 2021). Uppväxten i en stigmatiserad stadsdel, där arbetslöshet och bidragsberoende är en del av vardagen och där omvärldens blick på det egna bostadsområdet är nedvärderande, leder till att många unga ser sig själva som andra klassens medborgare.…”
Section: Inledning: Segregation Skolans Misslyckande Och Mobilisering...unclassified
“…To graduate from upper secondary school implies difficulties for many students in need of special educational support. Furthermore, these students are overrepresented among adolescents that transit directly from school to unemployment (Gustafsson, Katz, & Österberg, 2016;Raggi & Chronis, 2006;Ungdomsstyrelsen, 2013). A lack of support in upper secondary school often results in poor selfconfidence and decreased motivation to attend school (Korhonen, Linnanmäki, & Aunio, 2014), and is an important reason for dropping out of school (Dooley & Schreckhise, 2016;Trampush, Miller, Newcorn, & Halperin, 2009).…”
Section: Education For Further Opportunitiesmentioning
confidence: 99%